2022
DOI: 10.1029/2022jc019350
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon Effects on the Vertical Chlorophyll Distribution on the Northern Shelf of the South China Sea

Abstract: Typhoons are known to induce strong ocean mixing and upwelling, bringing cold and nutrient-rich subsurface water to the surface layer. Cold subsurface water can generally lead to a decrease in sea surface temperature (SST) to the right of the typhoon track (Dickey et al., 1998;Price, 1981). The nutrient-rich subsurface water that is injected into the upper layer can stimulate phytoplankton growth and increase primary production (e.g., Babin et al., 2004;Lin et al., 2003;Walker et al., 2005). Reduced turbulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…The northeast current, influenced by the summer southwest monsoon, causes the flow of the PRP toward the northeast of the estuary (Gan et al, 2010), and the passage of typhoons disrupts the flow dynamics, resulting in an amplified impact of the PRP on the western side of the estuary (Supplementary Figure S3). These findings highlight the dominance of the advection process driven by typhoons in the occurrence of algal blooms, which dissipate as the flow field changes (Zhao et al, 2009;Fang et al, 2022;Feng et al, 2022). However, unlike the findings from previous studies, the temporal fluctuations in the Chla and NO3 concentrations appeared nearly synchronous, emphasizing direct Chla transport rather than a process of nutrientinduced phytoplankton growth.…”
Section: Influence Of Horizontal Advection On Ecological Elementscontrasting
confidence: 69%
See 3 more Smart Citations
“…The northeast current, influenced by the summer southwest monsoon, causes the flow of the PRP toward the northeast of the estuary (Gan et al, 2010), and the passage of typhoons disrupts the flow dynamics, resulting in an amplified impact of the PRP on the western side of the estuary (Supplementary Figure S3). These findings highlight the dominance of the advection process driven by typhoons in the occurrence of algal blooms, which dissipate as the flow field changes (Zhao et al, 2009;Fang et al, 2022;Feng et al, 2022). However, unlike the findings from previous studies, the temporal fluctuations in the Chla and NO3 concentrations appeared nearly synchronous, emphasizing direct Chla transport rather than a process of nutrientinduced phytoplankton growth.…”
Section: Influence Of Horizontal Advection On Ecological Elementscontrasting
confidence: 69%
“…The CoSiNE model was initially developed to simulate marine geochemical processes in the equatorial Pacific Ocean (Chai et al, 2002) and has been applied at various spatial scales, including the North Pacific Ocean (Xiu and Chai, 2012), SCS (Pan et al, 2017) and PRE (Fang et al, 2022). Additionally, the model has been applied to study the responses of marine ecosystems to typhoon events (Pan et al, 2017;Fang et al, 2022). The parameter settings of the biogeochemical model for this study can be found in Table 1.…”
Section: Hydrodynamic-biogeochemical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of Chl-a near the shore is influenced by monsoon patterns, upwelling events, and the influx of coastal rivers. Consequently, a pronounced increase in Chl-a concentration occurs in proximity to the shoreline, whereas variations in daily sea surface wind speed far from the coast do not significantly impact Chl-a levels [30,31]. Before the typhoon, the average concentration of Chl-a in the South China Sea study area was 0.37 mg/L (Table 4).…”
Section: Surface Chlorophyll Response Analysismentioning
confidence: 98%